Freshwater fish diversity from Siberut Island, a small island in the western part of Sumatra, Indonesia - DEWI IMELDA ROESMA; DJONG HON TJONG; DYTA RABBANI AIDIL; FURQAN DWIKI LINTANG PRAWIRA; ANDRI SAPUTRA (Society for Indonesian Biodiversity, 2024)
Abstract. Roesma DI, Tjong DH, Aidil DR, Prawira FDL, Saputra A. 2024. Freshwater fish diversity from Siberut Island, a small island in the western part of Sumatra, Indonesia. Biodiversitas 25: 836-845. Indonesia is an archipelagic country with thousands of islands, including small islands with a variety of biodiversity, such as freshwater fish. Data and information on the fish biodiversity of small islands in the western part of Sumatra are limited, including Siberut Island. A study on freshwater fish diversity in Siberut Island was carried out using morphological and molecular methods. The study was conducted on seven rivers in the North and South Siberut Districts, Siberut Island. The study obtained 676 individuals, including 34 species, 26 genera, 16 families, and 10 orders. Oxudecidae is the family with the largest species (8), and Rasbora jacobsoni has the highest number of individuals (341). Species richness ranged from 2 to 18 species per site and was highest in the Srilanggai River. Siberut Island has low-moderate freshwater fish diversity. As many as 90 DNA barcodes of individuals from 34 species have been submitted to the Barcode of Life Data System. Freshwater fish groups do not receive enough attention from local communities and the government because of the richness of marine fish on Siberut Island. Apart from functioning as evidence of species richness, the results of this study are also useful for local communities' education.